Evaluation of Soil Test Recommendation for High Yielding Wheat For Soils of Sriganganagar Region - Kumar, Vinod; Mathur, G S; Seth, S P (Annals of Arid Zone, 2016)
The soil test recommendation in light texture soils of Sriganganagar region were evaluated in 19bS-69 and 1969-70 rising wheat (Kalyan sona) as o test crop. The application of nitrogen and phosplatic fertlizers over the soil test recommendations did not increase the grain yield in both the years. The application of 45% N + 30% P2O5 over soil test recommendations slightly decreased the grain yield in the year 1969-50. However, straw yield was significantly increased by the applicantion of 45% N over the STR. The application of K2O5 on soil rest basis did not give any response in in both the years (STR = soil test recommendation).